The use of smartwatches to record sleep and activity in bipolar disorder : a pilot study - Ísabella Guðmundsdóttir 1994- (2023)
This pilot study examines the use of smartwatches in therapy for bipolar disorder in Iceland. The watches tracked sleep and daily activity and compared the results to self-assessment of depression and mania. Sleep and activity are core symptoms of depression and mania in patients suffering from bipolar disorder. The goal of this pilot study was to observe if longer sleep and less activity, measured with smartwatches, would be associated with more symptoms of depression and if the smartwatch data would indicate less sleep and more activity among people with symptoms of mania. Participants were seeking treatment at the bipolar outpatient service at Landspítali University Hospital. Data from four patients were analyzed. The watches were worn continuously for four weeks. The findings indicate that most participants were in remission from their disorder and only one participant met clinical cut-offs for depression at the time of the study. The smartwatch data demonstrated that the participant with depression had an average sleep duration of 11 hours, while other participants had a mean sleep duration of approximately 8 hours. Furthermore, the anomalous participants’ mean step count was less than 1500 steps per day, compared to over 3000 steps among the other participants. The mania cut-off score was met at one timepoint for two participants. However, there was no evidence of mania based on the sleep and step count data, therefore mania was not analyzed in great detail. There was high variability observed in sleep patterns and step count for all participants, per previous research on bipolar patients. This pilot study on the use of smartwatches for patients with bipolar disorder shows promise for future treatment. A more extensive study including participants with more varied symptoms will aid in understanding the association between bipolar symptoms and sleep and activity. Keywords: bipolar disorder, smartwatches, mHealth, depression, mania, sleep, activity